Plasma concentrations of oleoylethanolamide in a primary care sample of depressed patients are increased in those treated with selective serotonin reuptake inhibitor-type antidepressants. (1st May 2019) - Romero-Sanchiz, Pablo; Nogueira-Arjona, Raquel; Pastor, Antoni; Araos, Pedro; Serrano, Antonia; Boronat, Anna; Garcia-Marchena, Nuria; Mayoral, Fermin; Bordallo, Antonio; Alen, Francisco; Suárez, Juan; de la Torre, Rafael; et al.
Abstract: Oleoylethanolamide (OEA) is a non-cannabinoid acylethanolamide with multiple physiological roles that has been proposed to have antidepressant-like activity in preclinical models. OEA shares biosynthetic pathways with anandamide (AEA) a transmitter involved in affective disorders and anxiety in humans. However, although the participation of OEA in depression has been proposed, both, the contribution of OEA to the depressive phenotype and the effect of antidepressant therapy on circulating levels of this and related non-cannabinoid acylethanolamides in humans are basically unknown. The main objective of this study is to compare the plasma concentrations of OEA and related acylethanolamides in a sample of primary care patients with depression (n = 69) with those of healthy non-depressed patients (n = 47). At the time of admission to the study, 22 patients were under selective serotonin reuptake inhibitor (SSRI) antidepressant treatment and 47 patients were not receiving any type of intervention. In addition, plasma concentrations of the endocannabinoid 2-AG and two related monoacylglycerols were monitored. Plasma OEA concentrations were found to be elevated in depressed patients and to correlate with somatic symptoms of depression. Plasma concentrations of both, AEA and 2-AG, were found to be elevated also in depressed patients. Further analysis demonstrated that the elevation observed in the plasma concentrations of both, OEA and 2-AG, was associated to SSRI antidepressant therapy at the time of recruitment. Further clinical research is needed to understand whether SSRI-induced elevations in OEA levels contribute to the response to SSRI in depressed patients as described in preclinical models. Highlights: Oleoylethanolamide (OEA) is a non-cannabinoid acylethanolamide with antidepressant activity in preclinical models. Depressed patients recruited at a primary care setting were found to have increased plasma levels of OEA and 2-AG. This was observed only in patients with current antidepressant treatment with selective serotonin reuptake inhibitors (SSRI). The concentrations of OEA correlated with somatic symptoms of depression. A potential role for OEA in the pharmacological actions of SSRI is discussed.